Rancang Bangun Particle Counter untuk Monitoring Konsentrasi PM1, PM2.5 dan PM10 di Udara Berbasis IoT - Falahuddin, Muhamad Anda; Puloh, Asep; Sumeru, Sumeru; Arman, Muhammad; Ayu, Wirenda Sekar; Susilawati, Susilawati (Jurnal Otomasi Kontrol dan Instrumentasi, 2024)
Poor air quality is a serious health and environmental issue. Microscopic particles such as PM1, PM2.5, and PM10 cause respiratory disorders and other health problems. Therefore, accurate and continuous air quality monitoring is crucial to mitigate the impacts of air pollution. This research aims to design an Internet of Things (IoT)--based particle counter capable of real-time air quality monitoring and reporting via an online platform. The system utilizes a PMS5003 sensor to measure PM1, PM2.5, and PM10 concentrations precisely. Data from the sensor is processed by an ESP8266 microcontroller connected to the internet, enabling direct data transmission to an online platform for further analysis and visualization. Testing is done by creating a 1x1x1 meter testing chamber to simulate various environmental conditions and validate the device's performance. Results show that the particle counter provides accurate data, with an error rate of less than 10% compared to standard devices. The device demonstrates reliable operation across different environmental conditions, showcasing its robustness in practical applications. This IoT-based particle counter offers an innovative solution for effective and efficient air quality monitoring. It is expected to significantly contribute to human health protection efforts and minimize the adverse environmental impacts of air pollution.